معاشرتی فلاح میں صحت کا کردار اسلامی تعلیمات کے تناظر میں: The Role of Health in Social Welfare in the Context of Islamic Teachings - Naveeda Khanam, (Al-Amīr Research Journal for Islamic Studies, 2024)
The role of health in societal welfare holds significant importance within Islamic teachings. Islam emphasizes the holistic well-being of individuals, encompassing both physical and mental health. Islamic principles advocate for maintaining health through a balanced lifestyle, proper nutrition, regular physical activity, and mental peace. In this context, health is not only a personal asset but also a communal responsibility, as the well-being of individuals directly impacts the prosperity of society. The teachings of the Quran and Hadith encourage seeking medical knowledge, maintaining hygiene, and ensuring a healthy environment. This paper explores how Islamic values and practices contribute to the promotion of health as a key factor in societal welfare, emphasizing the interconnection between individual health and the collective prosperity of society. Keywords: Role, Health, Social Welfare, Islamic Teachings